Character Education in a Children’s Short Story Book entitled “Linda has a Papaya Garden” - Ayu Anindia Hizraini; Retno Winarni; Sri Yamtinah (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to describe structures and the values of character education in the children's storybook "Linda has a Papaya Garden" by Astry Lestari. This research uses qualitative research with a descriptive analysis method. The technique used in collecting data is through documentation and the technique used to analyze the data is content analysis. The results showed that the children's storybook "Linda has a Papaya Garden" by Astry Lestari has a story structure consisting of themes, characters and characterizations, settings, plots and messages. Meanwhile, the educational values contained in the children's storybook are religious, honest, disciplined, hardworking, creative, curious, appreciating achievement, caring for the environment, and responsibility. The message of this story conveys the importance of preserving humility and toughness as the basic values to instil in children's development.